Implementasi Penggunaan Metode Talaqqi Sebagai Upaya Meningkatkan Mutu Hafalan Juz 30 Bagi Siswa Di MTS Al-Ma’arif Rakit Banjarnegara - Khoerunisa Nur Afifah, Adira; M. Hizbul Muflihin, M. Hizbul (Jurnal Pendidikan Agama Islam, 2025)
Improving the quality of Quran memorization is an important part of strengthening religious educationat the madrasah level. MTs Al-Ma'arif Rakit Banjarnegara, through its tahfizh class program, seeks toimprove the quality of students' memorization of Juz 30 by implementing the talaqqi method. Thismethod emphasizes a direct learning process between teachers and students through musyafahah,namely reading and listening to Quranic verses face to face. This approach is believed to not only trainmemorization skills but also improve reading, tajwid, and shape students' spiritual discipline. Thisstudy aims to determine how the implementation of the talaqqi method in an effort to improve the qualityof student memorization. The study was conducted using a descriptive qualitative approach, throughobservation, interviews, and documentation. The data analysis techniques used were data collection,data editing, data presentation, data verification, and drawing conclusions. The results of the study indicate that the implementation of the talaqqi method to improve memorization of Juz 30 for studentsat MTs Al-Ma'arif Rakit Banjarnegara involves three stages: scheduling and setting dailymemorization targets; implementing the talaqqi method, which consists of four steps: teacher andstudent preparation; reading verses by the teacher (sima'), repeating the reading (takrar), and practicingindependently; and evaluating the method, which includes several steps: time evaluation, murajaahevaluation, and memorization evaluation. Obstacles in implementing the talaqqi method includedifferences in memorization abilities among students and boredom while waiting for the roll call.